2019
DOI: 10.1038/s42003-019-0312-y
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: SnRK2 protein kinases represent an ancient system in plants for adaptation to a terrestrial environment

Abstract: In the original published PDF version of the article, the labels on the graphs in Figure 2c were inadvertently swapped. The error has been corrected in the PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…NPFs were found in Chlorophyta Volvox carteri, all tested Streptophyte, and land plants, but not in red algae (Figure 4). Molecular and genetic evidence revealed that core ABA signaling networkz consisting of PYR/PYL/RCARs, PP2Cs, and SnRK2s of early land plants is comparable to that of Arabidopsis (Tougane et al, 2010;Takezawa et al, 2015;Bowman et al, 2017;Briskine et al, 2017;Cai et al, 2017;Eklund et al, 2018;Jahan et al, 2019;Shinozawa et al, 2019). As a result, the ABA signaling network evolved before the land plants.…”
Section: Aba Biosynthesis and Signaling Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…NPFs were found in Chlorophyta Volvox carteri, all tested Streptophyte, and land plants, but not in red algae (Figure 4). Molecular and genetic evidence revealed that core ABA signaling networkz consisting of PYR/PYL/RCARs, PP2Cs, and SnRK2s of early land plants is comparable to that of Arabidopsis (Tougane et al, 2010;Takezawa et al, 2015;Bowman et al, 2017;Briskine et al, 2017;Cai et al, 2017;Eklund et al, 2018;Jahan et al, 2019;Shinozawa et al, 2019). As a result, the ABA signaling network evolved before the land plants.…”
Section: Aba Biosynthesis and Signaling Networkmentioning
confidence: 99%
“…Growing evidence has revealed the evolutionarily conserved roles of ABA and its biosynthesis and signaling systems from bryophytes to angiosperms that cause them to survive and thrive in terrestrial conditions (Sakata et al, 2014;Cuming and Stevenson, 2015;Shinozawa et al, 2019). However, our understating of ABA signaling processes leading to heavy metals detoxification in non-angiosperms is still limited.…”
Section: Evolution Of Gene Families For Aba-responsive Heavy Metals Amentioning
confidence: 99%